LAW PARADIGM DEVELOPMENT TO REDUCE HOUSING BACKLOG - Sihotang, Sudiman (JURNAL ILMIAH LIVING LAW, 2017)
There is a difference of paradigm between rural and urban people about house ownership, if urban society is influenced by Civil Code thinking where if one buys land at the same time he/she buys everything that is above it, including house building. Unlike the village community, the atmosphere of thinking about the land is influenced by customary law, which has a communal nature in which the land is owned by a citizen or otherwise known as ulayat land, so it can be understood that the minds of rural people about the house is not always merged with the land ownership, or ulayat can be built houses of some fellowship members. As a result of this paradigm, people should think of setting up funds to buy land if they want to buy a house, while the price of urban land is higher, and for the housing stake-holders, for example, housing developers, the land is used as a business commodity and a tool to achieve profits- the more so, if people want to buy a flat housing, you can imagine the meter price of the building will be charged to the land which is an integral part of the apartment unit. This raises several issues such as the number of backlog of housing is increasing, in 2015 recorded approximately reaches 14 million backlog. The governments target of providing a million homes is not achieved, including the construction of 1000 towers the year it is getting harder to achieve. This study aims to look at legal aspects that can provide solutions for the provision of housing, especially the Low Income Community (MBR) and Very Low Income Society (MBSR) so that the construction of a house is not just a project of a particular party, but a way for people to access home ownership. The method used is Sociological Jurisdiction with deep attention as well as Normative Juridical aspects as the related variables one and other.Keywords : Paradigm, Housing Law, Flat, Low-Income Community.